Evaluation of robenidine analog NCL195 as a novel broad-spectrum antibacterial agent - Ogunniyi, A.; Khazandi, M.; Stevens, A.; Sims, S.; Page, S.; Garg, S.; Venter, H.; Powell, A.; White, K.; Petrovski, K.; Laven-Law, G.; Tótoli, E.; et al. (Public Library of Science, 2017)
The spread of multidrug resistance among bacterial pathogens poses a serious threat to public health worldwide. Recent approaches towards combating antimicrobial resistance include repurposing old compounds with known safety and development pathways as new antibacterial classes with novel mechanisms of action. Here we show that an analog of the anticoccidial drug robenidine (4,6-bis(2-((E)-4-methylbenzylidene)hydrazinyl)pyrimidin-2-amine; NCL195) displays potent bactericidal activity against Streptococcus pneumoniae and Staphylococcus aureus by disrupting the cell membrane potential. NCL195 was less cytotoxic to mammalian cell lines than the parent compound, showed low metabolic degradation rates by human and mouse liver microsomes, and exhibited high plasma concentration and low plasma clearance rates in mice. NCL195 was bactericidal against Acinetobacter spp and Neisseria meningitidis and also demonstrated potent activity against A. baumannii, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae and Enterobacter spp. in the presence of sub-inhibitory concentrations of ethylenediaminetetra-acetic acid (EDTA) and polymyxin B. These findings demonstrate that NCL195 represents a new chemical lead for further medicinal chemistry and pharmaceutical development to enhance potency, solubility and selectivity against serious bacterial pathogens.